Research the Changes Across Three Phases of Pregnancy of Prolactin, Thyroid Hormones and Lipid Profile - Ali Abbas Ali; Adawia Fadhel Abbas (Indian Journal of Forensic Medicine & Toxicology, 2021)
Pregnancy allows the maternal blood to alter both the hormonal and biochemical material. This research was therefore aimed at investigating the shift in the profile of Thyroid stimulating hormone (TSH), triiodothyronine (T3), tetraiodothyronine (Thyroxin T4), prolactin and lipid during the three stages of pregnancy. The study included 30 pregnant women and 20 non-pregnant women as a control group (the age of women was 20-41 years). The study was performed from October to May 2017 at AL-Batool Teaching Hospital in Baqubah District, Diyala Governorate, Iraq. Hormones were assessed using an automated hormone analyzer (Cobase411, Roche, Germany) and the lipid profile was measured using an automated biochemistry analyzer (Cobase400Integra Plus, Roche, Germany). The findings revealed a substantial elevation of prolactin in the three phases of pregnancy (p<0.05). While T3, T4, total cholesterol (TC) and triglyceride (TG) showed no significant elevation (p>0.05) in the first trimester relative to the control group, TC and TG increased significantly (p<0.05) in the second and third stages of the trimester of pregnancy and T3 and T4 increased significantly (p<0.05) in the first trimester compared to the control group.